Does Facilitative Supervision Made Difference in PHC Readiness to Provide Emergency Maternal and Newborn Care: an Operational Research at Primary Health Centre of Ende District, Eastern Indonesia - Sangguana Marthen Jacobus Koamesah; Idawati Trisno; Nicholas Edwin Handoyo; Rr. Listyawati Nurina (Journal of Social Research, 2023)
Purpose: Government of Indonesia (GOI) has commitment to ensure that basic obstetric and newborn care is provided as to standard of care, through a pilot project of facilitative supervision conducted at 5 Primary Health Centre (PHC) of Ende district, in a series of combined online and onsite supervision during a period of 7 months, ended in December 2021. This operational research examined PHC’ readiness in providing emergency obstetric and newborn care, comparing intervened and control PHC. Methods: This present study used quasi experimental method, with Post-test Only Control Group design. Intervention of facilitative supervision only provided in one group, and assessment conducted in those 2 groups, comparing results between those groups. Unit analysis was PHC, 2 PHCs selected as intervened PHC, and 2 PHCs as control. Data were collected through direct observation using check list, assessment of patient’s records, and interview with several health workers. Results: In this operational study we compared the service coverage and readiness in providing emergency obstetric neonatal care, between PHC that received and not received intensive facilitative supervision in the previous 7 months. PHC in urban area handling very few obstetric complications but referred more cases to District Hospital (>90). However, intervened PHC provide obstetric complication care two times higher (8.33%) than control PHC (4.17%). Both intervened and control PHC in rural area, provide far more obstetric complication care (>60%) compared to those in urban area, with the coverage of referral case around 30-35% from total obstetric complication cases. Intervened PHC in rural area managing all neonatal complication cases, and shows the lowest percentage of neonatal death (1,2%) compare to other PHCs. Control PHC in rural area also managed 88.89% of neonatal complication cases, but has the highest percentage of neonatal death (4.17%). The significant difference between intervened and control PHC in the input side, lies in the availability of emergency team which should be minimal of 3 health workers consist of doctor, midwife and nurse; and availability of neonatal emergency kit. In the process side, the difference between intervened and control PHC is more obvious in rural area, the main difference lies in the unavailability of algorithm and SOP for post-partum bleeding, pre/eclampsia, and neonatal resuscitation at control PHC Conclusions: There is difference in the readiness of providing emergency maternal neonatal between intervened and control PHC only in rural area, indicate by higher compliance level value in the intervened PHC (77.14%) compared to control PHC (40%). The difference in the quality of care only obvious in rural area and in emergency neonatal care, indicate by 3,5x lower percentage of neonatal death in intervened PHC compared to the control PHC